Can an online expressive writing program support people with inflammatory bowel disease? A feasibility randomised controlled trial. (August 2022) - Skvarc, David; Evans, Subhadra; Cheah, Suiyin; Cranney, Madeleine; German, Bonnie; Orr, Rebecca; Emerson, Catherine; Olive, Lisa; Beswick, Lauren; Massuger, Wayne; Raven, Leanne; Mikocka-Walus, Antonina
Abstract: Background: We explored feasibility, acceptability and preliminary efficacy of an online writing intervention (WriteforIBD) against an active control condition for distress in people with inflammatory bowel disease (IBD) at the time of the COVID-19 pandemic. Methods: A feasibility RCT was conducted in 19 adults (89.5% female, aged 20–69 years) with IBD and mild-moderate distress. Participants allocated to the WriteForIBD group completed a 4-day 30-min writing program adapted for IBD. The active control group wrote about trivial topics provided by researchers. Feasibility was established based on the recruitment and retention while acceptability based on completion rates and a numeric rating scale. All participants completed measures of mental health and disease activity before and after the intervention (one week) and at follow-up three months after the study commencement. Results: The retention rate in the study was high (100% WriteForIBD; 82% control). All participants attended every session. 84.2% of participants were satisfied with the intervention. All participants reported a significant improvement in IBD-Control immediately after the intervention; F (2, 33.7) = 7.641, p  = .002. A significant interaction of group*time for resilience was noted, R 2  = 0.19, p  < .001, with the active control group reporting a significant decline in resilience from the first follow-up to three months while no significant change in resilience for the WriteForIBD group was recorded. Conclusions: Online expressive writing is potentially feasible and highly acceptable to people with IBD who report distress. Future large-scale trials should explore the intervention that is adapted from this feasibility study. Registration: id: ACTRN12620000448943p. Highlights: First writing intervention for distress in people with inflammatory bowel disease. No effects on distress, self-efficacy, social support and disease activity. WriteForIBD attenuated a decline in resilience that was observed in control group. A significant improvement in IBD-Control post-intervention in both groups noted.